The Legal History of the Ottoman Empire - Miller, Ruth (History compass, 2008)
Ottoman legal history has traditionally been a marginal field - and Ottoman law an ambiguous study hovering at the edges of a number of methodological voids. It is like any other field in that it has seen its share of conventions established, challenged, and re-imagined. But it is also relatively unique in that it has never assumed its own centrality. Indeed, if there has been a running theme in most legal histories of the Ottoman Empire, it is that the best way to define Ottoman law is by explaining what it is not. This article will address some of the comparative frameworks that have shaped Ottoman legal history, and discuss the ways in which these frameworks are now being re-evaluated.